Development of the "Pegasting" Module and the Effectiveness of Module Utilization for Intensive Assistance for Mothers in Preventing Stunting - Yustiari, Yustiari; Khalidatul Khair Anwar; Syahrianti Syahrianti; Pepi Hapitria; Uun Kunaepah; Halijah Halijah (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To develop the "Pegasting" Module and evaluate the effectiveness of module utilization in intensive assistance for Mothers in Preventing Stunting. METHODOLOGY: The Design involved research and development, utilizing a quasi-experiment (one-group pre-post test design). The location was 10 villages in the North Konawe Health Service Work Area. The total sample consisted of 90 participants. Determining the number of samples using the Slovin formula. The data were analyzed using a questionnaire based on the data collected from the research instrument. The pre-test and post-test results were compared using the Wilcoxon signed-rank test. The analysis was conducted using the SPSS Statistics 22 application. The inclusion criteria were mothers with toddlers who were mentally healthy, had visited a health centre, and were not illiterate. RESULTS: The module validation stage was conducted by media experts, achieving a score of 68.48% in the feasible category and 97.33% from material experts in the very worthy category. The study indicates that providing training significantly enhances the knowledge and behaviour of pegasting cadres, with p-values of 0.001 and 0.012, respectively. The experimental group showed a significant difference in knowledge before and after the intervention compared to the control group, with p-values of 0.002 and 0.001, respectively. CONCLUSION: The intervention had a significant impact on the behaviour of mothers in both experimental and control groups.